PENGEMBANGAN IDENTITAS VISUAL SEBAGAI UPAYA PENGUATAN BRANDING UMKM DESA CIKELAT - Novia, Irsa; Hidayat, Alfiansyah; Ahmad Gozali, Rizqi; Alamsyah, Zaenal (LPPM Universitas Nusa Putra, 2025)
This research aims to develop a strong visual identity as part of a brand strengthening strategy for Micro, Small and Medium Enterprises (MSMEs) in Cikelat Village. Cikelat Village is one of the rural MSME locations that faces challenges in terms of marketing and brand differentiation in the era of globalization and increasingly fierce competition. This research uses a qualitative approach with case studies as a methodology, involving MSME owners in the participatory visual identity design process. The research results showed that the measuring instrument used in this research was proven to be valid and reliable, with a calculated r value that was greater than the table r value, and a very high level of reliability based on the Cronbach's Alpha reliability coefficient. This shows that the measuring instrument is reliable in measuring the variables studied. The development of a visual identity is expected to provide significant benefits for Cikelat Village MSMEs, increasing brand impressions, building trust, and increasing sales and sustainable growth. This service also integrates a community empowerment approach with the aim of increasing the knowledge and skills of MSME owners, supporting the development of their businesses. The results of this research provide an important contribution in understanding the importance of developing visual identity in the context of empowering rural MSMEs and provide a basis for further action in supporting the growth of MSMEs in Cikelat Village.